Literature and moral theory - Hamalainen, Nora (Bloomsbury Academic, 2017)
"A comprehensive overview of the role of narrative literature in late 20th-century Anglo-American ethics, as part of a reconsideration of the roles of generalization and theory in moral philosophy."--Provided by publisher.